ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PEMANEN - Muhammad Thamrin; Desi Novita; Faisal Azhari Baldan Panjaitan (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This aim of study was to analyze the factors that affect employee productivity of harvester in PT. Eastern Sumatra Indonesia Bukit Maradja Estate. Sampling method using Proportionate Stratified Random Sampling is a way of sampling from the population members with random and stratified. Data analysis method used is rank spearman analysis and coefficient determinant. The results showed that there is a correlation between work motivation, work dicipline dan compensation on productivity of harvester in PT. Eastern Sumatra Indonesia Bukit Maradja Estate. Then based on the results obtained coefficient analysis determinant factor most strongly correlated to labour productivity is the factor of work motivation.   Keyword : work productivity, employees palm harvesters